FREQUENCY OF CT FINDINGS IN PATIENTS WITH MINOR HEAD INJURIES - IHSAN, QUA; KHAN, KA (Biological and Clinical Sciences Research Journal, 2024)
Minor head injuries are a common occurrence in emergency departments, often resulting from road traffic accidents, falls, and other blunt trauma incidents. While patients with a Glasgow Coma Scale (GCS) score of 13 to 15 are generally considered to have minor injuries, computed tomography (CT) imaging plays a crucial role in identifying potential intracranial complications that may not be evident clinically. Objective: This study aimed to evaluate the computed tomography (CT) findings in patients presenting with minor head injuries to determine the prevalence of intracranial complications. Methods: A cross-sectional study was conducted involving 86 patients presenting with minor head injuries at a tertiary care hospital. Minor head injuries were defined as having a Glasgow Coma Scale (GCS) score of 13 to 15. Patients with polytrauma, previous neurosurgery, or severe critical conditions were excluded. Clinical assessments included demographic information, injury mechanisms, and symptoms such as loss of consciousness, vomiting, headaches, and post-trauma seizures. All patients underwent CT scans, which were interpreted by radiologists blinded to clinical data. CT findings were categorized, and statistical analysis was performed to evaluate the prevalence of different intracranial injuries. Results: The mean age of the study participants was 40.27 years, with a male predominance (61.6%). Road traffic accidents were the most common cause of injury (44.2%), followed by falls (37.2%). CT scans revealed that 31.4% of patients had subgaleal hematomas, 11.6% had subdural hematomas, 8.1% had skull fractures, and 5.8% had brain contusions. Notably, 43% of the patients presented with normal CT findings, indicating the absence of acute complications. Conclusion: Although a substantial number of patients with minor head injuries had normal CT findings, the detection of significant intracranial conditions such as subgaleal and subdural hematomas emphasizes the importance of routine imaging in this patient population. Early detection through CT imaging is essential in guiding clinical management and preventing potential complications in patients with minor head injuries.